Droplet Microfluidics for Tumor Drug‐Related Studies and Programmable Artificial Cells. Issue 7 (7th May 2021) - Dimitriou, Pantelitsa; Li, Jin; Tornillo, Giusy; McCloy, Thomas; Barrow, David
Abstract: Anticancer drug development is a crucial step toward cancer treatment, that requires realistic predictions of malignant tissue development and sophisticated drug delivery. Tumors often acquire drug resistance and drug efficacy, hence cannot be accurately predicted in 2D tumor cell cultures. On the other hand, 3D cultures, including multicellular tumor spheroids (MCTSs), mimic the in vivo cellular arrangement and provide robust platforms for drug testing when grown in hydrogels with characteristics similar to the living body. Microparticles and liposomes are considered smart drug delivery vehicles, are able to target cancerous tissue, and can release entrapped drugs on demand. Microfluidics serve as a high‐throughput tool for reproducible, flexible, and automated production of droplet‐based microscale constructs, tailored to the desired final application. In this review, it is described how natural hydrogels in combination with droplet microfluidics can generate MCTSs, and the use of microfluidics to produce tumor targeting microparticles and liposomes. One of the highlights of the review documents the use of the bottom‐up construction methodologies of synthetic biology for the formation of artificial cellular assemblies, which may additionally incorporate both target cancer cells and prospective drug candidates, as an integrated "droplet incubator" drug assay platform. Abstract : This review summarizes the recent progress of droplet technologies in anticancer drug development. Microfluidic‐formed droplets are utilized in both tumor spheroid formation and smart drug delivery. This work also highlights the current trend of using artificial cells materials for drug metabolism studies. Finally, a novel 'droplet incubator' concept as a prospective anticancer drug screening platform is introduced.